Faktor-Faktor yang Mempengaruhi Komunikasi Orang Tua-Remaja dalam Isu Kesehatan Seksual dan Reproduksi: Tinjauan Literatur Sistematis - Nurul Fatimah Susanti; Hasrita Octaliana; Endah Purda Listya (Direktorat Politeknik Kesehatan Makassar, 2025)
Adolescents are individuals aged 10–18 years. Adolescents who have sufficient knowledge about sexual and reproductive health issues can make wise decisions and avoid risky behavior. Parents are the closest people to provide information, guide, and encourage adolescents in their attitudes toward reproductive health. Parent-adolescent communication plays an important role in reducing risky sexual behavior and preventing various sexual and reproductive health problems. The purpose of this study is to update and provide a comprehensive overview of the factors that influence parent-adolescent communication about reproductive health issues. A literature review was conducted using the PubMed and ScienceDirect databases. Article selection methods used PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and were reviewed using the PICO framework (Participants, Interventions, Comparisons, and Outcomes). Keyword searches used a combination of keywords with Boolean operators (AND). Out of 1,133 articles found, 306 were selected for the study objectives and abstracts. Subsequently, selection was conducted according to inclusion criteria. Inclusion criteria were articles published between 2020 and 2025, quantitative research design, written in English, and all articles were free and accessible. Analysis of the 6 articles revealed that factors influencing parental communication with adolescents about sexual and reproductive health include parental education (3 articles), parental knowledge (3 articles), adolescents' attitudes toward sexual and reproductive health issues, and adolescents' awareness of accessing information about sexual and reproductive health (3 articles). The results of this study indicate the need for integrated reproductive health education that targets not only adolescents but also parents through various strategies, such as regular counseling conducted by relevant health care facilities. This educational program should be designed to enhance parents' knowledge, communication skills, and confidence in discussing sexual and reproductive issues openly and age-appropriately. Keywords: Communication; Parents; Adolescents; Sexual and reproductive health